Application of Virtual Reality Technology (VR) in Practice Teaching of Sports Rehabilitation Major. Issue 4 (April 2021) - Fang, Man; You, Fan; Yao, Rongqi
Abstract: Patients who can receive rehabilitation training provide two types of feedback. This is the biggest advantage of virtual reality technology for rehabilitation training, and at the same time can improve the patient's perception of rehabilitation results. This article aims to study the application of virtual reality technology (vr) in sports rehabilitation professional practice teaching. This paper uses the research method of virtual scene position mapping. The virtual scene position mapping is based on the virtual realization technology of upper limb rehabilitation training, which is manipulated by the movement of the patient's upper limbs. In the experiment, all the students in the first and second classes of a sports rehabilitation major in a local university were subjected to theoretical tests and practical ability assessments to all the students in the first and second classes of the sports rehabilitation major. Experimental data shows that the excellent rate and passing rate of the experimental class's practical ability test are much higher than those of the control class. Therefore, it can be concluded that the application of virtual reality technology to sports rehabilitation teaching is beneficial to the improvement of learners' practical ability. The experimental results show that the test excellence rate of the experimental class is 24.2% higher than that of the control class, and the passing rate is 12% higher. Therefore, applying virtual reality technology to sports rehabilitation education can stimulate people's interest in learning. The virtual environment is very similar to the real world, and the motor skills learned in the virtual environment can be successfully transferred to the real world.